Identification of the Membrane-Associated Transporter Protein (MATP) Gene Polymorphism as Candidate Mutation for Albinism in Japanese Quail - Laksita Haniifah Pratiwi; Ratih Dewanti; Muhammad Cahyadi (Jurnal Ilmu-Ilmu Peternakan, 2023)
A pigmentation abnormality could be due to genetic mutation and trigger a disease related pigmentation deficiency such as albino which might be caused by mutation in membrane-associated transporter protein gene (MATP). The aim of this study was to identify polymorphism in the MATP exon 3 in Japanese quail. A total of nine Japanese quail consisting three brown plumage quail, three black plumage quail, and three albino quail were used in this study. Blood samples were used to extract the genomic Deoxyribonucleic acid (DNA) and used to amplify exon 3 regions of the MATP by polymerase chain reaction (PCR). The PCR products were then sequenced and analyzed. A total of 10 mutations were found, of which three mutations, g.4460G>A, g.4479G>A, and g.4514T>C, were within exon 3. These mutations were synonymous and non-synonymous. No specific mutation for albino was found in this study. In  summary those mutations did not specifically determine albinism in Japanese quail.